Is Routine Histopathological Examination of Appendix Mandatory? - Acharya, A; Basnet, RB; Singh, RR; Bastakoti, R; Paudel, SR (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: No age is immune for appendicitis and appendicectomy. Appendicectomy is one of the most common operations done all over the world. Emergency surgeries are more common than elective. Histopathological examination of every excised tissue is strongly recommended but trained manpower and laboratory for histopathological examination is not available in every hospital in our country.Methods: It is a prospective observational study of appendectomy performed at Bir Hospital, Kathmandu, Nepal country over a period of three years. Histopathological examination reports and preoperative findings were collected. Histopathological examination was performed by postgraduate pathologist at different hospitals and laboratory centres. Peroperatively appendices were categorized as non malignant looking appendix and suspicious malignant looking appendix by operating surgeons at different hospitals. Histopathological examination reports were compared with peroperative categorization.Results: Eight hundred and fifty five appendectomies performed during the study period were analysed. Eight hundred thirteen (95.1%) cases had non-malignant looking appendix and 42 (4.9%) cases had malignant looking appendix peroperatively. Seven (0.8%) cases were found malignant and 848 (99.2%) cases were found non-malignant on histopathology report. All seven (16.67%) malignant cases were from 42 suspicious malignant looking cases.Conclusion: Routine histopathology examination is mandatory for only peroperative suspicious malignant looking appendix.